Repeated evolution of asymmetric genitalia and right-sided mating behavior in the Drosophila nannoptera species group - Acurio, Andrea E.; Rhebergen, Flor T.; Paulus, Sarah; Courtier-Orgogozo, Virginie; Lang, Michael (BMC ecology and evolution, 2019)
Background Male genitals have repeatedly evolved left-right asymmetries, and the causes of such evolution remain unclear. The Drosophila nannoptera group contains four species, among which three exhibit left-right asymmetries of distinct genital organs. In the most studied species, Drosophila pachea, males display asymmetric genital lobes and they mate right-sided on top of the female. Copulation position of the other species is unknown. Results To assess whether the evolution of genital asymmetry could be linked to the evolution of one-sided mating, we examined phallus morphology and copulation position in D. pachea and closely related species. The phallus was found to be symmetric in all investigated species except D. pachea , which displays an asymmetric phallus with a right-sided gonopore, and D. acanthoptera, which harbors an asymmetrically bent phallus. In all examined species, males were found to position themselves symmetrically on top of the female, except in D. pachea and D. nannoptera , where males mated right-sided, in distinctive, species-specific positions. In addition, the copulation duration was found to be increased in the nannoptera group species compared to closely related outgroup species. Conclusion Our study shows that gains, and possibly losses, of asymmetry in genital morphology and mating position have evolved repeatedly in the nannoptera group. Current data does not allow us to conclude whether genital asymmetry has evolved in response to changes in mating position, or vice versa.